Output fixed‐time synchronization of discontinuous coupled neural networks with multiple output couplings. (4th May 2022) - Wei, Ruoyu; Cao, Jinde; Duan, Peiyong; Gorbachev, Sergey
Abstract : This paper is concerned with the output fixed‐time synchronization of coupled neural networks (CNNs) with multiple output couplings. Two types of network model are considered: the CNNs with coupling delays and the CNNs without coupling delays. In addition, discontinuous activation is taken into account so that the model is more general. Then, by employing a new type of fixed‐time control lemma, two flexible control strategies are designed to realize the output fixed‐time synchronization of the multiweighted CNNs, and less conservative criteria are obtained. Moreover, the settling time can be estimated with more accuracy than most existing literature. Lastly, two simulations are designed to testify the correctness of the proposed theorems.